THE EFL TEACHERS’ PERCEPTIONS OF LEARNER AUTONOMY AND ITS DEVELOPMENT IN AN INDONESIAN CONTEXT - Agustina, Dwi; Gleeson, Margaret; Hubbard, Gillian (LLT Journal: A Journal on Language and Language Teaching, 2022)
Creating long-life learners has become a long-term educational goal in many educational settings including Indonesia. An initial step towards this goal is to develop autonomy in students. Currently, learner autonomy or independence in learning has been promoted in higher education through the concept of Merdeka Belajar (freedom of learning) by the Minister of Education and Culture. In high schools, the 2013 curriculum has also emphasized learner autonomy development. Thus it is necessary to look back at how teachers perceived the concept of learner autonomy long before the concept of Merdeka Belajar was introduced. This article reports a quantitative study that investigated English teachers’ perceptions of learner autonomy and its development in Indonesia. This study was conducted in 2014 using a questionnaire and involved 145 high school English teachers in Magelang Regency, Central Java, Indonesia. The findings revealed that these Indonesian teachers held positive perceptions of learner autonomy and strongly supported psychological elements of learner autonomy. These EFL teachers also showed strong support for social aspects of autonomy. These junior high school teachers perceived social interaction and cooperation as important for promoting learner autonomy in the Indonesian context.